The Influence of Work Motivation and Teacher Emotional Intelligence on Teacher Performance at SMP Negeri 2 Sampit in the 2021/2022 Academic Year - Jayadi, Jayadi; Mahmuddin, Mahmuddin; Wiguna, Alivermana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine: (1) the effect of work motivation on teacher performance at SMP Negeri 2 Sampit in the academic year 2021/2022, (2) the influence of emotional intelligence on teacher performance at SMP Negeri 2 Sampit in the academic year 2021/2022, and (3) the combined effect of work motivation and emotional intelligence on teacher performance at SMP Negeri 2 Sampit in the academic year 2021/2022. The population in this study consisted of all teachers at SMP Negeri 2 Sampit in the academic year 2021/2022, totaling 11 individuals. The study used saturated sampling, and data collection was conducted using a questionnaire. The data analysis technique employed was multiple linear regression. The results of the study showed that: (1) work motivation had an effect on teacher performance at SMP Negeri 2 Sampit in the academic year 2021/2022, with a t-value greater than the t-table value (t = 3.180 > 2.306), (2) there was no significant effect of emotional intelligence on teacher performance at SMP Negeri 2 Sampit in the academic year 2021/2022, with a t-value smaller than the t-table value (t = 0.966 < 2.306), and (3) there was a combined effect of work motivation and emotional intelligence on teacher performance at SMP Negeri 2 Sampit in the academic year 2021/2022, with a t-value greater than the t-table value (t = 25.713 > 4.26).